MEMBERSHIP AUTOMATION SYSTEM AND LIBRARY USING RFID AT FACULTY OF ENGINEERING UNTAG SEMARANG - Budi Hartono; Toni Wijanarko Adi Putra; Nuris Dwi Setiawan; Agung Surono (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2022)
This study aims to build a library system application that can be used in the library of the Faculty of Engineering UNTAG Semarang based on an RFID card. From the background of the problem, namely, the process of borrowing and returning books is quite long, because to search for borrowed books the librarian must go to the bookshelf and look for the title of the book to be borrowed. The difficulty in making reports, because it is done after the library activities are finished, does not automatically coincide with the process of borrowing and returning services. Starting from the problems above, and paying attention to the number of daily visitors in the library that must be served, the authors propose to create a library service application using an RFID tag that can help the process of searching for member data and library books quickly.